1978
DOI: 10.4319/lo.1978.23.4.0767
|View full text |Cite
|
Sign up to set email alerts
|

The herbivorous habits of Mysis relicta in Lake Michigan 1

Abstract: IIerbivorous feeding by Mysis relicta on three size fractions of natural phytoplankton from Lake Michigan was measured from the change in concentration of chlorophyll a. Mysis fed primarily on the largest size fraction. When offered only the largest size fraction, Mysis fragmented the material and the fragments were observed as increases in the smallest size fraction Diuptomus ashlandi, which could feed only on the smallest size fraction, is a possible recipient of such fragmented cells or chains. A simple com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 6 publications
2
67
0
Order By: Relevance
“…2c) . These observations are similar to those of Beeton (1960), Bowers & Grossnickle (1978), and Bowers & Vanderploeg (1982) . Furthermore, sonar recorded an aggregation of small fish from the surface to 12 m between 2100 h August 29 and 0500 h August 30 (Fig .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…2c) . These observations are similar to those of Beeton (1960), Bowers & Grossnickle (1978), and Bowers & Vanderploeg (1982) . Furthermore, sonar recorded an aggregation of small fish from the surface to 12 m between 2100 h August 29 and 0500 h August 30 (Fig .…”
Section: Resultssupporting
confidence: 79%
“…Studies of the vertical community structure in Lake Michigan have shown that maximum concentrations of planktivorous fish, omnivorous mysids, and chlorophyll a often coincide during summer stratification (Brooks & Torke, 1977;Bowers & Grossnickle, 1978 ;Janssen & Brandt, 1980). Relationships between distributions of all these taxa and the microcrustaceans in the lake have not, however, been reported previously.…”
Section: Introductionmentioning
confidence: 86%
“…Bowers & Grossnickle (1978) felt that differential grazing pressure through selectivity might be a mechanism influencing phytoplankton community composition. In this light, possible interactions between Mesopodopsis slabberi and the large diatoms Asterioneila glaciahs and Aulacodiscus luttonii require further investigation as both species are potentially capable of generating accumulations in the surf zone.…”
Section: Discussionmentioning
confidence: 99%
“…Clutter (1966) suggested that the accumulation of a large amount of detrital food outside the breaker zone could be the major factor influencing the distribution of nearshore mysids such as Metamysidopsis elongata. Bowers & Grossnickle (1978) and Grossnickle (1979) have shown that Mysis relicta in Lake Michigan feeds on phytoplankton at night by migrating to the subsurface layer containing maximum chlorophyll a concentrations. A similar feeding strategy, involving shoreward migration at night to behind the breaker line where rip currents deposit Anaulus birostratus and detrital food material, may be practised by Mesopodopsis slabberi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation